A fruição dos direitos humanos da mulher e a Lei Maria da Penha - Marcondes, Thereza Christina Vieira (2010)
The issues related to domestic violence and gender inequality require interest for several reasons. The promulgation of Law 11,340, of 07 August 2006, appointed by the President of "Maria da Penha Maia" prompted many debates, both in the legal world and in society. With three years of duration, the mood is not quieted. Persist sometimes heated discussions. This justifies studies and reflections on the law that expanded the concepts of domestic violence against women, proposed a system of protection and the concentrated focus of attention on the victim. The woman, as victim of this violence is considered from the perspective of a complete individual: that is, deserves the protection of the law in the physical, psychological, sexual, property, moral. The Law of Domestic and Family Violence against Women proposed the creation of mechanisms to deter and prevent abuse within families and establish guidelines to combat discrimination, affirming the Human Rights of women, while recognizing the vulnerability of women under domestic relations or family. The constitutional principles of equality and dignity require the guarantee of Human Rights of Women, derived from the process of specialization and individualization of Human Rights. Law 11.340/06 was edited to meet the recommendations, in order to achieve an effective response to domestic violence and conceived from the perspective of gender, seek multidisciplinary solutions to the issue of violence against women, including measures awareness and training of professionals in various areas to give concreteness to a legal system out for Human Rights, in accordance with the democratic State of Law